(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the immunological response of tuberculin test and diagnostic BCG test inoculation given simultaneously to children suffering from tuberculosis. Study Design: Comparative – Cross sectional. Place and Duration of Study: This study was carried out at the Department of Paediatric Medicine, Nishtar Hospital Multan from 6 April 2011 to 5 Oct 2011. Materials and Methods: Fifty patients with tuberculosis were selected. Relevant data of cases including personal data, presenting complaints, physical examination finding and results of all the relevant investigations were collected. We injected 0.1 ml tuberculin intradermally on ulnar surface of right forearm and 0.1 ml BCG vaccine intradermally on deltoid muscle of left side. Both the BCG and tuberculin tests were performed at the same time by the same doctor. All information was recorded in a specifically designed proforma. Results: 26 patients were male and 24 female. Out of 50 patients; BCG test was positive 36 patients and was negative in 14 patients. Mantoux test was positive in 26 patients and was negative in 24 patients. Both BCG and mantoux tests were positive in 26 patients. Ten patients had a positive BCG test where Mantoux test showed negative results. Both tests were negative in 14 patients. Conclusion: BCG skin test is more superior to Mantoux test as a diagnostic tool in paediatric age group patients suffering from various types of tuberculosis.